Impact of Task Diversity in Intermediate-Task Training on Zero-Shot Cross-Lingual Transfer Performance - Assignee Research (Assignee Research, 2026)
Multilingual pre-trained models have achieved remarkable performance on cross-lingual transfer learning. Some multilingual models such as mBERT, have been pre-trained on unlabeled corpora, therefore the embeddings of different languages in the models may not be aligned very well. In this paper, we aim to improve the zero-shot cross-lingual transfer performance by proposing a pre-training task named Word-Exchange Aligning Model (WEAM), which uses the statistical alignment information as the prior
Machine-generated literature synthesis.